(untitled) (World Bulletin of Public Health, 2024)
The relationship between the factor of changes in vascular function, autonomic dysfunction in restless legs syndrome and chronicization of cerebral circulation and the pathomechanism underlying these relationships remains unclear and debatable. By the method of clinical and neurological symptoms, instrumental and using questionnaires (scales), we have shown that restless legs syndrome affects the mechanism of regulation of changes in large and small vessels, both peripheral and central, which underlie ischemic events and influence their severity. At the same time, changes in endothelial structure play a central role in the onset and progression of cerebrovascular disease, and in recent years, many scientists have considered the endothelium as a separate organ, taking into account its volume and function. The result of the obtained analysis, with the understanding of the pathomechanism of VAS as one of the causes of lower limb vascular damage with parallel changes in the formation and development of chronic cerebrovascular impairment, should provide therapeutic strategies to preserve vascular integrity, and be an important strategic direction for stroke prevention.